The impact of Sarcocystis infection on lamb flavor metabolites and its underlying molecular mechanisms - Zhang, Kang; Teng, Huan; Zhu, Li; Ni, Bin; Jiewei, Lai; Shanshan, Li; Yunong, Zhao; Guo, Xiao; Lamu, DanQu (Frontiers in Veterinary Science, 2025)
IntroductionMeat flavor is a critical factor for consumers to evaluate meat quality and a key determinant of its market value. Sarcocystis spp. are widely distributed parasitic protozoa that infect livestock, leading to reduced meat quality, fur, and fiber, and causing significant economic losses. However, most studies focus on the pathogenic mechanisms and epidemiological characteristics of Sarcocystis, with limited research on its specific impact on meat quality and flavor, particularly the underlying molecular regulatory mechanisms.MethodsThis study investigated the effects of Sarcocystis infection on meat flavor and its molecular mechanisms in Tibetan sheep using flavor metabolite analysis and transcriptomic approaches. Tibetan sheep raised under uniform conditions were divided into four groups based on infection severity: normal, low-infection, moderate-infection, and high-infection. Leg muscle samples were collected for flavor metabolite analysis and transcriptome sequencing. Differentially expressed metabolites (DEMs) and differentially expressed genes (DEGs) were identified, and KEGG pathway enrichment analysis was performed to explore how Sarcocystis infection regulates gene expression, affecting lipid, amino acid, and energy metabolism, ultimately altering the production and accumulation of flavor metabolites.ResultsThe results showed that Sarcocystis infection significantly altered the composition of flavor metabolites in Tibetan sheep meat as infection severity increased. Phenolic and acidic metabolites were markedly upregulated, intensifying bitterness and sourness, while ketone and lactone metabolites were downregulated, reducing fatty and creamy aromas. Transcriptomic analysis identified 574 DEGs, including upregulated genes such as MAPK12, COX6A2, and RXRA, which are involved in lipid metabolism, fatty acid oxidation, and thermogenesis, and downregulated genes such as COX2, COX3, and ADIPOQ, which are associated with mitochondrial function and energy metabolism. These gene expression changes disrupted lipid and amino acid metabolism, leading to imbalances in the synthesis and accumulation of flavor compounds.DiscussionThis study systematically revealed the significant effects of Sarcocystis infection on the meat flavor of Tibetan sheep and its underlying molecular mechanisms. The findings provide new insights into the metabolic regulation induced by parasitic infection and offer a theoretical basis for mitigating the adverse effects of Sarcocystis infection on meat quality.